Empirical Therapy of Complicated Pyelonephritis - V. A. Beloborodov; V. A. Vorobev; P. V. Opanasyuk (Acta Biomedica Scientifica)
The aim of the research was to analyze the effectiveness of empirical therapy in patients with established complicated upper urinary tract infection (complicated pyelonephritis).Materials and methods. 51 patients who were treated in 2018 in the urological department of the Irkutsk City Clinical Hospital N 1 were subjected to a retrospective study. The average age of patients was 55.9 ± 16.9 years.Results. Successful empirical therapy was considered in the absence of correction of the treatment regimen and the normalization of clinical blood and urine tests. Of the patients included in the study, successful empirical therapy was found in 24 (47%) patients, and required correction in 27 (52.9 %) patients. Cephalosporins as monotherapy were ineffective in 24 (57.1 %) patients, carbopenems – in one (25 %), fluoroquinolones – in all (100 %). Aminoglycosides showed the best result as a combination therapy with cephalosporins – 100 % (n = 3) of success. Based on multivariate logistic regression analysis, it was established that the detection of microhematuria and uremia in clinical analyzes upon admission to the hospital increases the likelihood of empirical monotherapy with third-generation cephalosporins by 20 % and 27 %, respectively.Conclusion. It is advisable to refrain from the use of monotherapy with fluoroquinolones and third-generation cephalosporins until more information is available about the resistance of uropathogens in the population of the Irkutsk region. Patients with impaired renal function require particularly close attention of the clinician when choosing a scheme for the empirical treatment of complicated pyelonephritis.